Influence of air humidity on the particle formation of single mannitol-water droplets during drying - Griesing, Matthias; Grosshans, Holger; Gutheil, Eva (Chemie - Ingenieur - Technik, 2016)
The effect of process parameters on the droplet drying process, which is crucial for tailor-made particle designs in spray drying processes, was investigated. Because of the challenging observability in spray towers single droplet experiments were carried out using acoustic levitation. The influence of the air humidity on the particle and solid layer formation of single mannitol-water droplets and temperature profiles of the complete drying process were experimentally determined. Also, the influence of the air humidity on the solid layer formation and the droplet temperature evolution was investigated.